Safety, feasibility, and application of intraperitoneal gas-based hyperthermia beyond 43°C in the treatment of peritoneal metastasis: An in-vivo pilot study - Diakun, Agata; Khosrawipour, Tanja; Mikolajczyk-Martinez, Agata; Nicpoń, Jakub; Thelen, Simon; Kiełbowicz, Zdzisław; Prządka, Przemysław; Liszka, Bartłomiej; Kulas, Joanna; Zielinski, Kacper; Li, Shiri; Lau, Hien; et al. (Frontiers in Oncology, 2022)
Background: 43°Celsius (C) is currently the highest temperature used in the treatment of peritoneal metastasis (PM). Despite sufficient data on water- based hyperthermic solutions in PM treatment, there is currently no information on gas-based hyperthermia extending beyond 43°C. This study is the first to provide in-vivo data on different organ systems during and after intraperitoneal gas-based hyperthermia beyond 43°C. The aim of this study is to explore in-vivo feasibility, safety, and efficacy of this novel concept from a biological perspective. Methods: For this study, three swine were subjected to laparoscopy and subsequent gas-based intraperitoneal hyperthermia at 48°, 49° and 50°C under a high-flow air stream. Intraoperative data from multiple temperature sensors were analysed. Additionally, intraoperative anaesthesiologic and gasometrical data was analysed. Postoperatively, swine were monitored for one week and laboratory work-up was performed on postoperative days 1, 3 and 7. Results: During gas-based intraperitoneal hyperthermia, anesthesiologic parameters did not exhibit critical values. No intra- or postoperative complications were observed. Distinct temperature measurements on the skin, cystohepatic triangle and esophagus did not display any temperature increase. Postoperative laboratory workup did not show any changes in hemoglobin, white blood cell count, platelets, or kidney function. Discussion: Based on our data, there are no safety concerns for the application of gas-based hyperthermia between 48 - 50°C. In fact, no critical systemic temperature increase was observed. With respect to possible limitations, further in-vivo studies are required to evaluate whether gas-based intraperitoneal hyperthermia may be a therapeutic option for PM patients.